Computational studies on PLK1 delta gene in cancer diseases - K Aarthi, J Febin Prabhu Dass, Preeti Tabitha Louis, I Arnold Emerson (Journal of Applied Pharmaceutical Science, 2015)
Cancer is a group of diseases involving abnormal cell growth with the potential to invade or spread to other parts of the body. Polo-like kinases (Plks) are a family of conserved serine/threonine kinases involved in the regulation of cell cycle progression through G2 and mitosis. One of them being PLK1, it’s over expression leads to a variety of cancers. Plk1 delta, an uncharacterized protein sequence found in UniProt was studied and found to consist of the N-terminal portion of plk1gene. The 3D protein structure of PLK1 delta was modeled and then the predicted structure was validated. Molecular dynamics simulation was performed to find the stability of the protein. The modelled protein was docked to BI 2536, an inhibitor of Plk1 to obtain conformation of least binding energy. The interacting sites between the protein and inhibitor were also analyzed.
Keywords: PLK1 delta, molecular docking , cancer therapy.